Association of cesarean delivery timing with pelvic floor muscle function and urine incontinence: A propensity score‐matched study. Issue 1 (27th December 2022) - Chen, Yiyao; Xu, Chuangchuang; Saiding, Qimanguli; Chi, Xiaolei; Chu, Lei; Wang, Xianjing; Chen, Xinliang
Abstract: Pelvic floor dysfunction is a common gynecological disease that adversely affects women's quality of life and mental health. Delivery is considered a significant independent risk factor for pelvic floor dysfunction. Surface electromyography (sEMG) values for the pelvic floor muscles (PFM) have been shown to differ according to different delivery modes. This study aimed to compare sEMG results between intrapartum and antepartum cesarean delivery (CD), 42–60 days after delivery. Data of women who underwent CD at the International Peace Maternity and Child Health Hospital were collected from September 2021 to December 2021. Myotrac Infiniti System was used to measure the electromyographic activity of PFM after 42–60 days of parturition. Propensity score matching (1:1) was applied to achieve a balance in baseline data between the two groups (intrapartum and antepartum CD). A total of 200 paired cases were selected for statistical analysis. In the propensity score‐matched analysis, there were no statistically significant differences in PFM sEMG between women with antepartum or intrapartum CD ( p  > 0.05 for all). We observed similar results with postpartum urinary incontinence (24 [12.0] vs. 21 [10.5]; adjusted odds ratio (aOR), 1.12 [95% confidence interval (CI) 0.60–2.12]; p  = 0.717) and stress urinary incontinence (12 [6.0] vs. 14 [7.0]; aOR, 0.80 [95% CI 0.35–1.80]; p  = 0.596) as outcomes. After excluding participants with intrapartum CD when the cervix was dilated <6 cm, all sEMG of PFM had a comparable level of risk in both the antepartum and intrapartum CD groups. There were no significant differences in sEMG of the PFM and the incidence of urinary incontinence between patients undergoing intrapartum or antepartum CD. Excluding women who underwent intrapartum CD when the cervix was dilated to <6 cm produced little change in results. Thus, different opportunities for CD may not impact the sEMG of the PFM and the incidence of urinary incontinence. Abstract : In the present study, patients who underwent the first CD at the International Peace Maternity and Child Health Hospital from September 2021 to December 2021 were included for analyzing the effect of intrapartum CD compared to antepartum CD on the activity of the PFM. The patients were divided into an antepartum CD group and an intrapartum CD group according to delivery mode. The propensity score‐matched cohort included 400 primiparous women who underwent CD, 200 each in the antepartum and intrapartum CD groups. In the propensity score‐matched analysis, there were no statistically significant differences in PFM sEMG between women with antepartum or intrapartum CD.